Sosialisasi Legalitas Usaha MIkro Kecil dan Menengah Dengan Pembuatan Nomor Induk Berusaha di Desa Sukomakmur Magelang: Socialization Micro, Small, and Medium Enterprises Legality with Business Identification Number in Sukomakmur Village Magelang - Ambarwati, Ambarwati; Alfianto, Achmad Nur; Fitriyani, Yeny (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Micro, small and medium enterprises (MSMEs) have an important role in economic growth in Indonesia, especially in rural areas. However, many MSMEs have difficulty advancing their businesses because there is still a lack of information in rural areas. This village community empowerment activity aims to support the economy of the Sukomakmur Village community, especially for MSMEs in Sukomakmur Village. The efforts made by the author are by assisting in making the NIB. Activities are carried out from July to August. The assistance provided is by holding workshops and assistance in making the NIB starting from filling in the form for making the NIB to making it on the OSS website. This activity was attended by 21 business actors consisting of 16 grocery stores, 4 food stalls, and 1 vegetable trader. In this mentoring activity, the approach used is the Asset-Based Community Development (ABCD) method to legalize the businesses of MSMEs. The ABCD method is an approach to strives to realize social order in society and community development for its environment. It can also be called Community-Driven Development (CDD). This assistance results in a Business Identification Number owned by every business actor. This assistance shows that workshops and assistance in making business legalization can be the right solution to advance MSMEs in Sukomakmur Village.